2013
DOI: 10.1099/jmm.0.046771-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaplasma phagocytophilum in ruminants, rodents and ticks in Gansu, north-western China

Abstract: The zoonotic rickettsial pathogen Anaplasma phagocytophilum has a broad geographical distribution and a high degree of biological and clinical diversity. To determine the prevalence of Anaplasma phagocytophilum in the Gannan Tibetan Autonomous Prefecture of Gansu Province, north-western China, four ruminant species, one rodent and one tick species were examined for Anaplasma phagocytophilum infection. DNA from Anaplasma phagocytophilum was detected by nested PCR in blood samples from 21/49 sheep (42.9 %), 35/9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
(28 reference statements)
3
24
1
Order By: Relevance
“…Furthermore, among all the risk factors associated, tick presence and unhygienic condition were highly associated with infection as shown by coefficient of correlation (Table 2). Indirect ELISA Real-time PCR [2,8,[16][17][18]. In small ruminants, the overall prevalence rate was 33.87%…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, among all the risk factors associated, tick presence and unhygienic condition were highly associated with infection as shown by coefficient of correlation (Table 2). Indirect ELISA Real-time PCR [2,8,[16][17][18]. In small ruminants, the overall prevalence rate was 33.87%…”
Section: Resultsmentioning
confidence: 99%
“…The first wild animals observed to be positive for A. phagocytophilum in east China were Apodemus peninsulae, A. agrarius, and Eutamias sibiricus (15). A. agrarius was subsequently found to be infected with A. phagocytophilum in west China (9). This evidence appeared to support the role of the genus Apodemus as reservoirs in the natural life cycle of A. phagocytophilum.…”
Section: Discussionmentioning
confidence: 81%
“…Dogs from both urban and rural habitats in Brazil were found to be positive for A. phagocytophilum (12). In addition, goats and sheep were highly infected with A. phagocytophilum in China (9). In Nanchang, however, a previous examination could not detect the presence of A. phagocytophilum.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…(APsd) detected in sika deer and cattle (Jilintai et al, 2009), is very common in Japan. AP-sd has also been reported as a strain of A. phagocytophilum in Japan and China (Kawahara et al, 2006;Liu et al, 2012;Yang et al, 2013), deer type A. phagocytophilum (Wu et al, 2015) or an Anaplasma species closely related to A. phagocytophilum (Ybañez et al, 2013). Despite the last report showing high prevalence in sika deer, N45% (10/ 22) (Jilintai et al, 2009), AP-sd has never been reported from humans.…”
Section: Introductionmentioning
confidence: 89%